(3QSGdI aj eSCdI GdCLRGAs - (3ejQRG CHh GdbGSe cdGfJQs
(3ChdgG (B:s
(3HYO Ef GNJdahG ai Cf EfHGJ GdeCehQ s
(3BNQgG (B:s
(3dCf GdefTGA dh cGf JQc GdhGLH ai MGdI GdCLRGA s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI GdfLa (B(130) s
Keywords: (3GdadSaI hGdefWbs